Taxonomic notes on genera allied to Pleurotroppopsis (Hymenoptera: Eulophidae, Entedoninae) with description of a new genus from the Afrotropical region - Gumovsky, Alex (Zootaxa, 2007)
Afrotroppopsis risbeci Gumovsky gen. & sp. nov. (Hymenoptera: Eulophidae, Entedoninae), a parasitoid of leafminers on Khaya senegalensis in Senegal and Ochna pulchra in South Africa, is described. The new genus belongs to the complex of genera allied to Pleurotroppopsis Girault, 1913, which includes also the genera Apleurotropis Girault, 1913, Kratoysma Bouček, 1965, Zaommomentedon Girault, 1915, Platocharis Kerrich, 1969, Schizocharis Kerrich, 1969, and Parahorismenus Girault, 1915. The following nomenclature changes are proposed: the generic name Atullya Surekha & Narendran, 1988 is synonymized with Pleurotroppopsis (syn. nov.); two species are moved from Schizocharis to Zaommomentedon: Z. milletiae (Kerrich, 1969) comb. nov. and Z. newbyi (Kerrich, 1969) comb. nov. Relationships within and outside the complex, generic concepts and taxonomic values of some characters are discussed.